2023
DOI: 10.3390/land12040932
|View full text |Cite
|
Sign up to set email alerts
|

Land Consumption Classification Using Sentinel 1 Data: A Systematic Review

Abstract: The development of remote sensing technology has redefined the approaches to the Earth’s surface monitoring. The Copernicus Programme promoted by the European Space Agency (ESA) and the European Union (EU), through the launch of the Synthetic Aperture Radar (SAR) Sentinel-1 and the multispectral Sentinel-2 satellites, has provided a valuable contribution to monitoring the Earth’s surface. There are several review articles on the land use/land cover (LULC) matter using Sentinel images, but it lacks a methodical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Sentinel-1 is a SAR satellite developed by the European Space Agency (ESA) and forms part of a two-satellite Earth observation system [46]. It consists of two satellites named S1A and S1B launched on 3 April 2014 and 25 April 2016, respectively [44].…”
Section: Synthetic Aperture Radarmentioning
confidence: 99%
See 1 more Smart Citation
“…Sentinel-1 is a SAR satellite developed by the European Space Agency (ESA) and forms part of a two-satellite Earth observation system [46]. It consists of two satellites named S1A and S1B launched on 3 April 2014 and 25 April 2016, respectively [44].…”
Section: Synthetic Aperture Radarmentioning
confidence: 99%
“…While the X-band (8~12 GHz) might not be commonly used for direct lithology identification in remote sensing applications, it can still contribute to lithology identification efforts by providing valuable information through high-precision topographic data. Sentinel-1 [46], polarimetric SAR (Pol-SAR) [47], and Phased Array type L-band SAR (PALSAR) [45,48] are highly favored for lithological mapping. However, studies have shown that radar data generally has lower spatial resolution compared to optical images, and the acquisition and processing of radar data can be complex [45].…”
Section: Introductionmentioning
confidence: 99%
“…Optical distant sensing images are not only unique from images in common natural scenes but also have huge differences between various targets in their own sample images. This phenomenon of huge differences in appearance and shape makes it difficult to preset the anchor frame of the network, resulting in the result that the target is missed [20][21][22].…”
Section: Introductionmentioning
confidence: 99%